KOLABORASI MAHASISWA DAN MASYARAKAT DALAM PROGRAM PENANAMAN POHON UNTUK LINGKUNGAN BERKELANJUTAN DI KELURAHAN TONROKASSI, KECAMATAN TAMALATEA, KABUPATEN JENEPONTO - Abubakar, Zulfiana; Muhammad Firdaus (Bajang Institute, 2025)
This Community Service Activity (PKM) aims to increase community participation in environmental conservation through collaboration between students and residents in a tree planting program in Tonrokassi Village, Tamalatea District, Jeneponto Regency. The problems faced include a reduction in green open spaces, land use change, and low public awareness of the importance of reforestation. The activity was carried out in several stages: socialization, planting technique training, planting implementation, formation of environmental monitoring groups, as well as evaluation and monitoring. A total of ±50 mango, mahogany, ketapang, and trembesi tree seedlings were successfully planted with the involvement of students, village officials, youth organizations, and local residents. The results of the activity showed an increase in community knowledge and skills in planting and caring for trees, accompanied by a growing collective awareness to preserve the environment. The level of community participation reached ±85%, exceeding the initial target of 70%. The involvement of students proved effective in mobilizing community participation through an educational and participatory approach. This program had an ecological impact in the form of environmental greening and a social impact in the form of increased community responsibility for nature conservation. In the future, similar activities are expected to be expanded with an increase in the number of seedlings and strengthened cross-party collaboration.